Pengukuran Tingkat Efektivitas Mesin pada Komponen Silinder Arm Kobelco SK 200-10 melalui Implementasi (TPM) dan Metode OEE - Prasetiyo, Agung Dwi; Sundari, Susanti; Suwarni, Putri Endah (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Recurrent failures of the arm cylinder on the Kobelco SK 200-10 excavator at PT. XZ have resulted in increased downtime, decreased equipment performance, and higher maintenance costs. This study aims to evaluate equipment effectiveness through the implementation of Total Productive Maintenance (TPM) using the Overall Equipment Effectiveness (OEE) method. Measurement results for the period September–December 2024 indicate an OEE value of 38.97%, with availability of 82%, performance of 50.46%, and quality of 93.75%, suggesting that the equipment performance remains suboptimal, particularly in terms of performance . Six Big Losses analysis reveals that the largest losses are caused by reduced speed losses at 52.08% and average equipment failure losses of 13.96%. The main contributing factors are identified as machinery conditions, work methods, environmental factors, and operator involvement. Therefore, improving equipment effectiveness can be achieved through more disciplined preventive maintenance, refinement of operating procedures, and increased operator participation in daily maintenance activities. Keywords: Kobelco SK 200-10, OEE, Six Big Losses, TPM